(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the key determinants of digital banking Services that influence customer perception. As the banking industry increasingly shifts towards digital platforms, understanding the factors that shape customer perceptions is crucial for service providers aiming to enhance satisfaction and loyalty. Using a multiple regression analysis, the study identifies and examines various independent variables, including efficiency, system availability, fulfillment, privacy/security, responsiveness, website design, contact, and customer trust, and their respective impacts on the dependent variable—customer perception. Data was collected through a cross-sectional survey targeting users of digital banking services. The findings reveal that website design and customer trust are the most significant predictors of customer perception, with fulfillment and responsiveness also playing notable roles. In contrast, factors such as efficiency, system availability, privacy/security, and contact had less influence. The results offer valuable insights for banking institutions to prioritize customer-centric digital strategies and improve service delivery, thus fostering a better customer experience in an increasingly competitive digital environment.